Assessing the Effect of Plastic Granules on Mechanical Properties of Clay Soil for Road Subgrade. - Nasasira, Ezra (Kabale University, 2023)
Soi I sta bi Ii zati on can be explained as the alteration of the soil properties by chemical or physical means in order to enhance the engineering quality of the soil. The objectives of the soil stabilization were to increase the bearing capacity of the soil, its resistance to weathering process and determination of optimum plastic granules to be used which was done by use of controlled compaction. This new technique of soil stabilization can be effectively used to meet the challenges of society, to reduce the quantities of waste, producing useful material from non-useful waste materials. Plastic granules were used as a reinforcement to carry out the standard proctor compaction and CBR tests while being mixed with clay soil to improve its mechanical properties. A series of Standard proctor tests and California Bearing Ratio (CBR) tests were carried out on randomly reinforced soil by varying percentages of plastic granules (0%, 3%, 6%, 9%, 12% and 15%) by the weight of dry soil. As these materials are non-biodegradable, they have considerable life and huge potential in providing solutions to complex engineering problems. Clay soil was classified as CH or A- 7-6(16)in accordance with Unified Soil Classification System and AASHTO on a plasticity chart. The experimental results have clearly shown a significant improvement in the MDD and reduction in optimum moisture content. Finally, there was an increase in CBR values with the increase of plastic granules addition and then started to decrease and of which the optimum CBR value was determined from the graph of CBR values against percentages of plastic granules and was found out to be 3.1at 11% plastic granules addition.